hsa-miR-33-5p as a Therapeutic Target Promotes Apoptosis of Breast Cancer Cells via Selenoprotein T - Zhuang, Wei; Liu, Jianhui; Li, Wenjin (Frontiers in Medicine, 2021)
Objective: Increasing evidence suggests that microRNA (miRNA) participates in regulating tumor cell apoptosis. We aimed to observe the effect of hsa-miR-33-5p on apoptosis of breast cancer cells and to explore its regulatory relationship with SelT. Methods: RT-qPCR was used to examine the expression of hsa-miR-33-5p and Selenoprotein T (SelT) both in breast cancer tissues and cells. MCF-7 and MDA‐MB‐231 cells were transfected with hsa-miR-33-5p mimics or si-SelT. Then, flow cytometry assay was carried out to examine apoptosis of cells. Furthermore, SelT and apoptosis-related proteins including Caspase3, Caspase8, Caspase9, Bax and Bcl-2 were detected via RT-qPCR and western blot. Luciferase reporter assay was utilized for assessing whether SelT was targeted by hsa-miR-33-5p. Results: Down-regulated hsa-miR-33-5p was found both in breast cancer tissues and cells. After its overexpression, MCF-7 cell apoptosis was significantly promoted. Furthermore, our data showed that miR-33-5p elevated apoptosis-related protein expression in MCF-7 cells. Contrary to hsa-miR-33-5p, SelT was up-regulated both in breast cancer tissues and cells. SelT expression was significantly inhibited by hsa-miR-33-5p overexpression. Luciferase reporter assay confirmed that SelT was a direct target of hsa-miR-33-5p. SelT overexpression could ameliorate the increase in apoptosis induced by hsa-miR-33-5p mimics. Conclusion: Our findings revealed that hsa-miR-33-5p, as a potential therapeutic target could accelerate breast cancer cell apoptosis.